E24 Frontostriatal Abnormalities In Huntington's Disease: An Fmri Study. (17th September 2014) - Mason, S; Zhang, J; Rowe, J; Barker, R; Hampshire, A
Abstract : Background: Executive dysfunction is present from early in the disease process in HD although there is little consensus as to the nature and extent of these deficits. Aims: To evaluate planning and working memory ability across disease stages in HD from pre-manifest to advances disease. Methods: The computerised one touch Tower of London task was used in a large cross-sectional population of HD patients ranging from pre-manifest to late stage disease (n = 108); a small subgroup of whom were followed longitudinally (n = 40). In a separate study 20 pre-manifest HD gene carriers and 23 healthy controls completed the Tower of London whilst undergoing functional imaging. Results: Analysis of the cross-sectional data showed that task accuracy reduced with advancing disease especially for the harder 4 and 5 move problems. However, the absence of changes in the longitudinal study suggests that the Tower of London is not sensitive to cognitive decline in manifest disease over a short period of follow-up (mean 1.3 years, 0.75 SD). Performance of pre-manifest HD gene carriers on the Tower of London did not differ from controls but their planning related BOLD response and functional connectivity were reduced. Conclusions: Changes in planning related neural responses precede the onset of disease and changes in performance on the Tower of London task. However, once behavioural abnormalities are observed, performance deteriorates but not at a rate that makes it useful for tracking cognitive decline over short periods of time.